Phase transfer ceria-supported nanocatalyst for nitrile hydration reaction - Gupta, Nikitra N.; Punekar, Amrin S.; Raj, Karthik Raja E. K.; Ghodekar, Medha M.; Patil, Vipul S.; Gopinath, Chinnakonda S.; Raja, Thirumalaiswamy (ACS Omega, 2019)
The present study elaborates the catalytic effect of rare-earth metal oxides (Sm2O3 and La2O3) over ceria as a support phase transfer catalyst. The synthesized catalysts have been subjected to different characterization techniques, such as field-emission scanning electron microscopy, high-resolution transmission electron microscopy, powder X-ray diffraction, N-2 adsorption-desorption (BET surface analysis), temperature-programmed desorption study (NH3/CO2-TPD), Fourier transform infrared, Raman analysis, and X-ray photoelectron spectroscopy to get better insights into the catalytic activity of the catalysts for hydration of nitrile.